2006
DOI: 10.1016/j.ejheart.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of risk markers predicts the incidence of sudden death in patients with chronic heart failure

Abstract: Background: Sudden death is common in chronic heart failure (CHF). Risk stratification is the first step for primary prevention. Aim: To evaluate the use of risk markers for estimating sudden death risk. Methods and results: We prospectively examined 680 stable patients with CHF. Risk markers were evaluated using the Cox's proportional hazard model in a stepwise manner. Ejection fraction < 30%, left ventricular end-diastolic diameter > 60 mm, brain natriuretic peptide > 200 pg/ml, non-sustained ventricular tac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…40 We also reported that LVDd >60 mm was one of the independent risk markers of SCD in CHF patients in the CHART-1 study. 41 In contrast, in the present CHART-2 study, LVDd >65 mm, but not LVDd >60 mm, was a significant risk factor on univariate and multivariate Cox hazard analysis. We consider that the difference between the CHART-1 and CHART-2 studies is due to the difference in the patients studied.…”
Section: 75contrasting
confidence: 49%
See 2 more Smart Citations
“…40 We also reported that LVDd >60 mm was one of the independent risk markers of SCD in CHF patients in the CHART-1 study. 41 In contrast, in the present CHART-2 study, LVDd >65 mm, but not LVDd >60 mm, was a significant risk factor on univariate and multivariate Cox hazard analysis. We consider that the difference between the CHART-1 and CHART-2 studies is due to the difference in the patients studied.…”
Section: 75contrasting
confidence: 49%
“…They showed that the annual mortality from sudden death was 11% in patients with ≥3 risk factors and 1.4% in patients with ≤2. 41 In the present study, the presence of cAF or LVDd ≥65 mm had higher relative HR and their combination achieved the highest HR.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Grimm et al found that NSVT with a duration of ≥5 beats was significantly associated with increased risk of major arrhythmic events including SCD 17. Furthermore, the heart rate in NSVT has been arbitrary,26, 27, 28 ranging from ≥100 to 150 bpm, and not associated with increased risk of life‐threatening arrhythmias and SCD in DCM 17, 18, 29. In our study, we arbitrarily defined NSVT as ≥5 consecutive ventricular premature beats with a rapid heart rate (≥150 bpm), corresponding to the median ventricular rate previously reported in our DCM population 29.…”
Section: Discussionmentioning
confidence: 99%
“…AR‐DCM phenotype was diagnosed by the presence of 1 of the following: (1) unexplained syncope (likely due to ventricular tachyarrhythmia),2, 14, 15, 16 (2) rapid nonsustained ventricular tachycardia (NSVT) defined as ≥5 consecutive ventricular beats,17 lasting <30 seconds, with a rate ≥150/min on 24‐hour Holter monitoring,18 (3) ≥1000 premature ventricular contractions (PVCs) in 24 hours1 or (4) ≥50 couplets in 24 hours 19. ICD implantation had been performed for primary prevention in selected patients with DCM considered at high risk for SCD (ie, persistent LV dysfunction with LVEF ≤35% and New York Heart Association class II or III while being treated with optimal medical therapy).…”
Section: Methodsmentioning
confidence: 99%